2005
DOI: 10.1111/j.1600-9657.2005.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical investigation of traumatic injuries in Yeditepe University, Turkey during the last 3 years

Abstract: The aim of this study was to evaluate etiology, types of traumatic dental injuries, treatment and to determine the incidence of complications according to dental injuries in patients who referred to Yeditepe University, Faculty of Dentistry, Istanbul, Turkey. The study was based on the clinical data of the 161 traumatized teeth in 92 patients. WHO classification slightly modified by Andreasen & Andreasen for dental trauma was used. The causes and localization of trauma, traumatized teeth classification, treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

44
89
5
22

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(160 citation statements)
references
References 23 publications
44
89
5
22
Order By: Relevance
“…There is a lesser incidence of dentoalveolar trauma as age increases 8,18 . This was also observed in the present as most cases of trauma occurred in patients aged 0 to 5 years (21.8%) and falling was the most frequent cause.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a lesser incidence of dentoalveolar trauma as age increases 8,18 . This was also observed in the present as most cases of trauma occurred in patients aged 0 to 5 years (21.8%) and falling was the most frequent cause.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on dentoalveolar traumas are generally performed at schools in large or middle-sized cities 2,4,5 , middle-sized hospitals 6 and Dental Schools 7,8 . The city of São Paulo in Brazil is the second largest in Latin America and is an outstanding national medical reference center.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] Laceration was the most common extraoral injury. This is easily explained since most of the traumas were caused by direct impacts, in which lips act as a shield.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][6][7][8][9][10][11][16][17][18] The first and foremost steps in treating a traumatized patient should be physical examination and medical history review. Data obtained from this survey showed that 40% of the patients denied systemic alterations, which is consistent with their mean age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation